Photodynamic therapy: Inception to application in breast cancer. (February 2017) - Banerjee, S.M.; MacRobert, A.J.; Mosse, C.A.; Periera, B.; Bown, S.G.; Keshtgar, M.R.S.
Abstract: Photodynamic therapy (PDT) is already being used in the treatment of many cancers. This review examines its components and the new developments in our understanding of its immunological effects as well as pre-clinical and clinical studies, which have investigated its potential use in the treatment of breast cancer. Highlights: Photodynamic therapy (PDT) uses light, photosensitizer and oxygen to elicit cell death. PDT has low toxicity, repeatability and apparent anti-tumour activity. PDT may mediate an immune response causing tumour cell death at distant sites. PDT has the potential to be combined with radiotherapy. Further clinical trials are waited to assess its use in breast cancer.